Sensory modulation and negative affect in children at familial risk of ADHD. (May 2021) - Keating, J.; Bramham, J.; Downes, M.
Abstract: Background/aims: Sensory modulation difficulties are commonly reported in patients with ADHD, however there has been little focus on the development of these difficulties in young children at a higher risk of later ADHD diagnosis. This study investigated whether children with a familial history of ADHD show greater sensory modulation difficulties. We also explored whether sensory modulation was linked to negative affectivity, which has been highlighted as a potential early marker of ADHD. Methods: Parents of children under 6 years with a family history of ADHD (n = 65) and no family history (n = 122) completed questionnaires on sensory modulation and temperament. Results: Children from families with ADHD were reported to display extreme patterns of hyperresponsiveness and hyporesponsiveness, relative to controls. No differences emerged for the sensory seeking domain. Some children within the high-risk group reported high scores across all three sensory modulation patterns. Regression analysis revealed that hyperresponsiveness predicted higher levels of negative affect. Conclusions/implications: This study is the first to report greater sensory modulation difficulties in children at familial risk of ADHD. Future research should establish whether children with sensory modulation and temperament difficulties in early childhood are more vulnerable to developing ADHD.